Evaluation of condylar surface CT values related to condylar height reduction after orthognathic surgery. Issue 8 (August 2021) - Ueki, Koichiro; Yoshizawa, Kunio; Saito, Yuki; Takayama, Akihiro; Baba, Nana; Kimura, Yujiro; Koizumi, Mai; Fujimoto, Kana; Iguchi, Ran; Sato, Momoko; Osada, Asami Hotta; Moroi, Akinori
Abstract: This study was performed to evaluate the relationship between condylar height reduction and changes in condylar surface computed tomography (CT) values in jaw deformity patients following orthognathic surgery. Mandibular advancement by sagittal split ramus osteotomy (SSRO) with Le Fort I osteotomy was performed in class II patients, and mandibular setback by SSRO with Le Fort I osteotomy was performed in class III patients. The maximum CT values (pixel values) at five points on the condylar surface and the condylar height, ramus height, condylar square, ramus angle, and gonial angle in the sagittal plane were measured preoperatively and 1 year postoperatively. Disc position was classified as anterior disc displacement (ADD) or other types by using magnetic resonance imaging (MRI). Ninety-two condyles of 46 female patients were prepared for this study. Their temporomandibular joints (TMJs) were divided into two groups based on class (46 joints in class II and 46 joints in class III) and two groups based on the findings (25 joints with ADD and 67 joints with other findings). ADD with and without reduction was observed in two joints in the class III group and in 23 joints in the class II group. The distribution of ADD incidence had not changed 1 year after surgery. Condylar height decreased 1 year after surgery in both class II patients (mandibular advancement) ( p < 0.0001) and class III patients (mandibular setback) ( p = 0.0306). Similarly, condylar height decreased 1 year after surgery both in patients who showed ADD ( p = 0.0087) and those with other types ( p = 0.0023). Significant postoperative increases at all angle sites on the condylar surface were found in the class II ( p < 0.05) and ADD ( p < 0.05) groups. This study showed that an enhanced condylar surface CT value might be one sign of condylar height reduction related to sequential condylar resorption, in combination with ADD.